REDUCTION OF LIFTED STITCH DEFECTS IN WIRE BONDING PROCESS THROUGH ROOT CAUSE ANALYSIS - Puspita, Widya Rika; Manurung, Anjunius; budiana, Budiana; Nur Sakinah Asaad; Jefiza, Adlian; Nakul, Fitriyanti; Putra, Irwanto Zarma; Diputra, Muhammad Naufal Airlangga; Illa Aryeni; Handri Toar; Anggraini, Ria (Jurnal Teknologi Dan Riset Terapan (JATRA), 2025)
Reliable connection inspection is crucial for the quality of semiconductor products. A frequent issue is stitch defects during wire bonding. To address this, an investigation was conducted using flow charts. Additionally, an analysis was performed by identifying root causes using the Fishbone Diagram method and the 5 Whys technique. After improvements, including targeted operator training, a significant reduction of 96.75% in stitch defects was achieved. This study demonstrates that the combination of root cause analysis methods and operator training effectively enhances the reliability of the wire bonding process and the quality of semiconductor products. This study did not account for environmental factors that might influence the wire bonding process, such as temperature and humidity variations. Therefore, the findings may be limited in settings with different environmental conditions.